Big Data : A Beginner's Introduction. - Sarangi, Saswat; Sharma, Pankaj ([Place of publication not identified] : Routledge India, 2019)
Big Data is everywhere. It shapes our lives in more ways than we know and understand. This comprehensive introduction unravels the complex terabytes that will continue to shape our lives in ways imagined and unimagined. Drawing on case studies like Amazon, Facebook, the FIFA World Cup and the Aadhaar scheme, this book looks at how Big Data is changing the way we behave, consume and respond to situations in the digital age. It looks at how Big Data has the potential to transform disaster management and healthcare, as well as prove to be authoritarian and exploitative in the wrong hands. The latest offering from the authors of Artificial Intelligence: Evolution, Ethics and Public Policy, this accessibly written volume is essential for the researcher in science and technology studies, media and culture studies, public policy and digital humanities, as well as being a beacon for the general reader to make sense of the digital age.
1. Big Data: What, Why and How? 2. Big Data and AI 3. What Big Data is not? 4. How Data Analytics works? 5. Big Data: The Applications 6. Why Big Data Matters? 7. The challenges with Big Data 8. Big Data: the Key Questions 9. Big Data: Is there a question mark on ethics? 10. The Future of Big Data.
OCLC-licensed vendor bibliographic record.
Keywords: Big data -- Social aspects; SOCIAL SCIENCE / Future Studies; SOCIAL SCIENCE / Popular Culture; SOCIAL SCIENCE / Media Studies